2020
DOI: 10.3389/fvets.2020.00108
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium avium Subspecies paratuberculosis Drives an Innate Th17-Like T Cell Response Regardless of the Presence of Antigen-Presenting Cells

Abstract: The gastrointestinal disease of ruminants is clinically known as Johne's disease (JD) and is caused by Mycobacterium avium subspecies paratuberculosis (MAP). An accumulative effect by insensitive diagnostic tools, a long subclinical stage of infection, and lack of effective vaccines have made the control of JD difficult. Currently lacking in the model systems of JD are undefined correlates of protection and the sources of inflammation due to JD. As an alternative to commonly studied immune responses, such as t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 59 publications
0
8
0
Order By: Relevance
“…Moreover, the immune regulatory role of IL-10 has been considered to contribute to the persistence of MAP in the host immune system. Recently, the Th17-like response has been thought to be a major response to MAP infection associated with granuloma formation [33][34][35]. Early expression of Th17-induced cytokines such as IL-17a is associated with activation of innate T lymphocytes induced by IL-1β, IL-6, and IL-23 produced by phagocytic cells [9].…”
Section: Plos Onementioning
confidence: 99%
“…Moreover, the immune regulatory role of IL-10 has been considered to contribute to the persistence of MAP in the host immune system. Recently, the Th17-like response has been thought to be a major response to MAP infection associated with granuloma formation [33][34][35]. Early expression of Th17-induced cytokines such as IL-17a is associated with activation of innate T lymphocytes induced by IL-1β, IL-6, and IL-23 produced by phagocytic cells [9].…”
Section: Plos Onementioning
confidence: 99%
“…While IFN-g has long been considered as a hallmark cytokine in providing protection against mycobacterial intracellular pathogens (45), its role as a sole cytokine in providing protection against mycobacterial pathogens has been challenged (46,47). Recent evidence indicates that Th17mediated immune responses also contribute to the early inflammatory responses to mycobacterial infection, thus potentially play a crucial role in providing protective immunity against M. tuberculosis and MAP (46,(48)(49)(50). The current results demonstrated that antigen-specific IL-17A levels (both at the protein and mRNA levels) were significantly upregulated in animals vaccinated with the rMAP fusion protein.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, increased IL-17 has been observed in plasma from cows that are both ELISA and fecal test-positive for antibodies to MAP (Dudemaine et al, 2014). Also, treatment of bovine peripheral blood mononuclear cells with MAP antigens has resulted in increased secretion of IL-17A (DeKuiper and Coussens, 2019), and MAP antigens induce increased expression of IL17A mRNA in cultured bovine T-cells (DeKuiper et al, 2020).…”
Section: Discussionmentioning
confidence: 99%